2013
DOI: 10.1200/jco.2012.46.2101
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Psychosocial Care Among Cancer Survivors in the United States

Abstract: Purpose Given the importance of psychosocial care for cancer survivors, this study used population-based data to characterize survivors who reported a discussion with health care provider(s) about the psychosocial effects of cancer and who reported using professional counseling or support groups (PCSG) and tested associations between receipt of psychosocial care and satisfaction with care. Patients and Methods We examined survivors of adult cancers from the 2010 National Health Interview Survey (N = 1,777). Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 50 publications
3
94
0
3
Order By: Relevance
“…Many AYA patients also report unmet practical support needs, such as assistance with health insurance, financial planning, transportation, childcare, and peer support, as well as unmet health care needs, including physical therapy and mental health services [24]. A 2010 National Health Interview Survey indicated that many patients are unaware of what psychosocial services are available [26].Thus it is important to assess and address the unique psychosocial needs of each individual patient. Care providers can also help AYA patients and their family members determine the role of the family in the patients' care.…”
Section: Psychosocial Aspects Of Aya Cancer Diagnosis and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Many AYA patients also report unmet practical support needs, such as assistance with health insurance, financial planning, transportation, childcare, and peer support, as well as unmet health care needs, including physical therapy and mental health services [24]. A 2010 National Health Interview Survey indicated that many patients are unaware of what psychosocial services are available [26].Thus it is important to assess and address the unique psychosocial needs of each individual patient. Care providers can also help AYA patients and their family members determine the role of the family in the patients' care.…”
Section: Psychosocial Aspects Of Aya Cancer Diagnosis and Treatmentmentioning
confidence: 99%
“…Although much of the data comes from studies of survivors of pediatric cancers, there is some evidence that the diets of AYA cancer survivors are suboptimal. Studies find that only between 16 and 54% of such survivors have the recommended amount of fat in their diets [61][62][63][64], 86% are consuming more than the recommended daily intake of sugar [64], and a low percentage are eating 5 or more servings of fruits and vegetables per day [26,[61][62][63].They are also less likely to meet physical activity guidelines than people in the general population, and they are less active and more sedentary than theirsiblings [26,[61][62][63][65][66][67][68].These behaviors are juxtaposed with observational evidence that physical activity not only improves quality of life but is also associated with prolonged survival for some types of cancer [69,70].…”
Section: Lifestyle Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer has a significant effect on the psychological wellbeing of ayas, and many of their psychosocial needs remain unmet 17,18 . Compared with their healthy peers, ayas with cancer are at higher risk of experiencing poor psychological well-being and distress that can last for many years after treatment 19 .…”
Section: Psychosocial Issuesmentioning
confidence: 99%
“…Institute of Medicine reports 1,2 and surveys of patients and care providers 3,4 suggest limited progress has been made in implementing recommendations that oncology practices have procedures in place to identify and assist patients who experience psychosocial problems. Efforts to date to improve the quality of psychosocial care have focused mostly on issuance of clinical practice guidelines for distress management 5 and accreditations standards designed to foster greater patient-centered care.…”
Section: Introductionmentioning
confidence: 99%